OSH Studens won first place in noise and ergonomic category of IH2C intervarsity short video competition organized by department of occupational safety and health (DOSH) - Faculty of Engineering Technology, . (Faculty of Engineering Technology, 2019)
In conjunction with the 5th Scientific Conference on Occupational Safety and Health (SciCOSH) 2018 organized by DOSH, twelve students from OSH program have been conferred as the champion for the IH2C Intervarsity Short Video Competition under the Noise and Ergonomic categories. The competition is divided into 3 categories namely Noise, Chemical and Ergonomic with a total of 115 entries from the nation Institution of Higher Learning (IHL). Safety Memeda supervised by Dr. Hanida Abdul Aziz comprises of KH Yik , LP Hang, Freshellla Fiona S, Alexandra J H, PK Kei and CM Yee competed in the Noise category and OSHCrew Gen9 supervised by Dr. Ezrin Hani Sukadarin comprises of Siti Fatiha MZ, Muhammad Amir Izwan AA, Nur Amira Z, Noor Aisya.